(untitled) (Health Renaissance, 2011)
The Inter Professional Education (IPE) is an innovative teaching learning intervention in Health Professions’ Education during which members of more than one health profession learn interactively together to improve collaborative practice and/health of the patients. Thus this approach provides positive outcomes for students enhancing their awareness towards other professional groups, improving knowledge and understanding of how to work in an inter professional team and strengthening their communication and collaboration skills. Within the hierarchical nature of many clinical settings, the aims of IPE courses intersect with socialization of health professional (HP) students into roles of responsibility and authority. The IPE in HP courses emphasizes the practice of frequent high quality communication, strong relationships and partnerships among health care providers to maximize the quality of care thus improving the efficiency of care thereby improving clinical outcomes. Health Professional Schools are this motivated to opt for inter professional education to improve the learning of the students, health care delivery and patient outcomes. Keywords: Inter professional relations; patient centered care; education DOI: http://dx.doi.org/10.3126/hren.v9i3.5591 HR 2011; 9(3): 201-206